Prescription of renin‐angiotensin‐aldosterone system inhibitors (RAASi) and its determinants in patients with advanced CKD under nephrologist care. Issue 7 (6th June 2019) - Pecoits‐Filho, Roberto; Fliser, Danilo; Tu, Charlotte; Zee, Jarcy; Bieber, Brian; Wong, Michelle M. Y.; Port, Friedrich; Combe, Christian; Lopes, Antonio A.; Reichel, Helmut; Narita, Ichiei; Stengel, Benedicte; et al.
Abstract: Renin‐angiotensin‐aldosterone system inhibitors (RAASi) are recommended for chronic kidney disease (CKD) patients. In this study, we describe RAASi prescription patterns in the Chronic Kidney Disease Outcomes and Practice Patterns Study (CKDopps) in Brazil, Germany, France, and the United States (US). 5870 patients (mean age 66‐72 years; congestive heart failure [CHF] in 11%‐19%; diabetes in 43%‐54%; serum potassium ≥5 in 20%‐35%) were included. RAASi prescription was more common in Germany (80%) and France (77%) than Brazil (66%) and the United States (52%), where the prevalence of prescription decreases particularly in patients with CKD stage 5. In the multivariable regression model, RAASi prescription was least common in the United States and more common in patients who were younger, had diabetes, hypertension, or less advanced CKD. In conclusion, RAASi prescription patterns vary by country, and by demographic and clinical characteristics. RAASi appear to be underused, even among patients with strong class‐specific recommendations. Although the reasons for this variation could not be fully identified in this cross‐sectional observation, our data indicate that the risk of hyperkalemia may contribute to the underuse of this class of agents in moderate to advanced CKD.